Structures of the West Lampung’s Wayak Oral Literature - . Armina (Bandar Lampung University (UBL), 2014)
Wayak is one of oral literature products used by West Lampung society, Wayak is usually in the form of monolog or dialog. People are interested to listen Wayak done in wedding ceremony, teenager party, local radio, and local television. The problem in this research is related to the struture used in Wayak so it becomes the popular literature in West Lampung. The purposes of this research is to describe the structure in Wayak as oral tradition. This research is categorized as qualitative research which is supported by ethnography consideration to analize this oral tradition in reconstruction the structure of culture in society who use Wayak. The data collecting was done through documentation, interview, and observation. In data collecting process, the researcher is as the key of instrument. The structure of Wayak in West Lampung society investigated in this research are (1) the parts of Wayak consist of introduction, content, and closing; (2) Wayak construction consist of four lines; (3) The total number of words and syllable in Wayak are three words and seven syllable; (4) Wayak has various tone pattern: ABAB, AAAA, and ABBB; (5) the voice-repetition in Wayak consist of two kinds of repetition: vocal and consonant; (6) the tone of Wayak is about invitation, suggestion, critic, selfish, happiness, and sadness; (7) the language style of Wayak consists of paralelisme, invertion, and elipsis; (8) The proverb words in Wayak are about metaphor, hyperbole, sinekdoke, and metaphor; (9) syntax formation of Wayak is the use of pronouns and use of affixes; (10) Wayak musical accompaniment is in the form of a single organ or tambourine; and (11) Wayak tempo consists of high-low and fast-slow tempo.